The role of early aggressive nutrition on growth of very preterm or very low birth weight infants - Insani, Nadia Dwi; Rohsiswatmo, Rinawati; Sjarif, Damayanti Rusli; Marsubrin, Putri Maharani Tristanita; Yuliarti, Klara; Gultom, Lanny Christine (Paediatrica Indonesiana, 2024)
Background Very preterm infants (<32 weeks gestational age) are at high risk of poor neurodevelopmental outcomes. Early aggressive parenteral nutrition (protein ³ 2g/kg/day) can reduce the incidence of malnutrition in very preterm infants. At present, Fatmawati General Hospital does not have a standard nutritional protocol for preterm infant. Objective To determine the difference in growth (days to regain birth weight and growth velocity) of very preterm (<32 weeks gestational age) or very low birth weight (VLBW) (<1500g) infants who were born and hospitalized in the Neonatal Unit of Fatmawati General Hospital, Jakarta, before and after applying early aggressive parenteral nutrition using a nutrition protocol from Cipto Mangunkusumo Hospital, Jakarta. Methods A quasi-experimental study was conducted on 23 very preterm or VLBW infants in the Neonatal Unit of Fatmawati General Hospital, from July to November 2019. Control group data were taken from medical records of very preterm or VLBW babies discharged from our unit from January 2018 – to June 2019 and compared to those of the intervention group. Results The intervention group regained their birth weight significantly faster than the control group [mean 7.43 (SD 3.5) vs. 16.73 (SD 5.1) days, respectively; (P=0.00)]. Mean growth velocity was also significantly higher in the intervention group than in the control group [14.6 (SD 6.0) vs. 8.9 (SD 6.9) gram/kg/day, respectively; (P=0.002)]. Conclusion Provision of early aggressive parenteral nutrition reduces the time to regain birth weight and leads to higher growth velocity in very preterm/VLBW infants.